THE IMPACT OF ARTIFICIAL INTELLIGENCE AND AUTOMATION: A LITERATURE REVIEW ON INDUSTRIAL TRANSFORMATION - Loso Judijanto; Mohammad Ahmad Bani Amer; Iyad Abdallah Al- Shreifeen (Adisam Publisher, 2023)
This research explores the impact of artificial intelligence (AI) and automation on industrial transformation through a comprehensive literature review. The findings show that AI and automation have the potential to improve operational efficiency, productivity and innovation across a range of sectors, including manufacturing, services, healthcare and finance. However, the application of these technologies presents significant challenges, such as the reduction of traditional employment, the need to develop new skills, and ethical and data security issues. The study highlights the importance of investment in technology infrastructure, workforce training, and organisational culture adaptation to reap the maximum benefits of AI and automation. In addition, mitigation strategies and the formation of strategic partnerships are recommended to overcome negative impacts and ensure the success of industrial transformation in the digital age.